Ewangelia prawdy (NHC I,3) – gnostycka homilia? - Myszor, Wincenty (Studia Pastoralne, 2026)
The Gospel is portraying truths in many decimal places of the spot height of the recited work. There are returns addressed to listeners, in the second person of the plural. Contents gnostic of work: incentives and cautions without gnostic show the mythology to initiation character of the homily.